Implementasi Penggunaan Media Sosial instragram Dalam Perpustakaan Perguruan Tinggi - Adilla, Nurul; Zuhri, Rifqa Amalia; Elvina, Syafira (Sci-tech Journal, 2023)
Technological developments are very fast, starting from technology 1.0 to now launching technology 5.0, this illustrates that technology in the world continues to develop rapidly, Indonesia itself also follows these developments, social media is one of the results of technological developments, social media is a tool that makes it easier for users to express themselves them, even now social media is used as a market place, promotion, and service. In this study, researchers took samples of libraries that use social media Instagram in managing libraries, as well as sharing information and services from libraries in tertiary institutions. Keywords: instagram, social media, library